Dynamics of Auxin and Cytokinin Metabolism during Early Root and Hypocotyl Growth in Theobroma cacao - Mboene Noah, Alexandre; Casanova-Sáez, Rubén; Makondy Ango, Rolande Eugenie; Antoniadi, Ioanna; Karady, Michal; Novák, Ondřej; Niemenak, Nicolas; Ljung, Karin (Plants (Basel, Switzerland), 2021)
The spatial location and timing of plant developmental events are largely regulated by the well balanced effects of auxin and cytokinin phytohormone interplay. Together with transport, localized metabolism regulates the concentration gradients of their bioactive forms, ultimately eliciting growth responses. In order to explore the dynamics of auxin and cytokinin metabolism during early seedling growth in Theobroma cacao (cacao), we have performed auxin and cytokinin metabolite profiling in hypocotyls and root developmental sections at different times by using ultra-high-performance liquid chromatography-electrospray tandem mass spectrometry (UHPLC-MS/MS). Our work provides quantitative characterization of auxin and cytokinin metabolites throughout early root and hypocotyl development and identifies common and distinctive features of auxin and cytokinin metabolism during cacao seedling development.
Keywords: root development; auxin; phytohormone metabolism; cytokinin; Theobroma cacao